2013
DOI: 10.3109/01443615.2013.831046
|View full text |Cite
|
Sign up to set email alerts
|

Myoinositol: A new marker of intrauterine growth restriction?

Abstract: Inositol is a cyclic sugar alcohol which occurs naturally in a variety of stereoisomers, the most common of which is myo-inositol. Inositol phosphoglycan molecules have been isolated from mammalian tissues and are a major component of the intracellular mediators of insulin action. The fetus with intrauterine growth retardation (IUGR) activates a series of adaptive mechanisms to increase the chances for survival, such as a saving of glucose to ensure nutrition of the vital organs, with a consequent reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
1
21
0
2
Order By: Relevance
“…Among the metabolites identified in the "galactose metabolism" pathway, the myo-inositol concentration had already been proposed as a marker of development of obesity and type 2 diabetes in human adults [14,26] and also as a marker of IUGR in humans [1,15] and pigs [40]. In these previous studies, a higher plasma or urine concentration of myo-inositol was associated with a higher risk of IUGR and, thus, with a lower maturity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the metabolites identified in the "galactose metabolism" pathway, the myo-inositol concentration had already been proposed as a marker of development of obesity and type 2 diabetes in human adults [14,26] and also as a marker of IUGR in humans [1,15] and pigs [40]. In these previous studies, a higher plasma or urine concentration of myo-inositol was associated with a higher risk of IUGR and, thus, with a lower maturity.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, in pigs, NMR metabolomic profiling performed on fetuses at 110 days of gestation has demonstrated that low-weight fetuses had a higher plasma concentrations of myo-inositol than high-weight fetuses [40]. Also, Dessì and Fanos [15] have suggested that, in fetus with IUGR, greater plasma concentrations of myo-inositol may reflect an altered glucose metabolism and that they were associated with a decrease in lipid synthesis and cell proliferation through the reduction in insulin secretion. Such effects then result in a lower birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…It can be hypothesized that reduced production of fetal insulin leads to an excretion of inositol from the intracellular compartment to the extracellular compartment with a subsequent increase of this metabolite in plasma and urine and a reduction inside the cells. In fact, in our studies that analyzed urine of IUGR and large for gestational age infants, its content was significantly increased compared to controls [1,47]. Plasma and urinary increase of this metabolite, often correlated to glucose intolerance and insulin resistance in adults, could also be considered as a valid marker of altered carbohydrate metabolism during fetal development in IUGR [48].…”
Section: Inositolmentioning
confidence: 97%
“…An altered glucid metabolism during fetal development in neonates with intrauterine growth retardation (IUGR) has recently been suggested to be reflected by the increase in extracellular myoinositol that may be considered a valid predictive marker of the development of obesity and type 2 diabetes (T2D) in adulthood [16, 17]. Inositol is in fact known as a secondary messenger of the insulin transducer signal; it is also known that insulin plays a role in favoring lipid and provide synthesis as well as cell growth [18]. In the case of fetal malnutrition (both too much and not enough), it is thus possible to hypothesize that at birth there is a situation of reduced sensitivity to insulin which may be revealed by an increase in extracellular inositol.…”
Section: Metabolomics and Nutrition In Neonatologymentioning
confidence: 99%